Π-Conjugated-polymer-based nanofibers through living crystallization-driven self-assembly: preparation, properties and applications. Issue 98 (24th November 2021) - Ma, Junyu; Lu, Guolin; Huang, Xiaoyu; Feng, Chun
Abstract : π-Conjugated-polymer-based nanofibers endowed with both topological merits from fiber-like nanostructures and structural merits from π-conjugated polymers represent one of the most exciting and rapidly expanding fields. Abstract : π-Conjugated-polymer-based nanofibers (CPNFs) of controlled length, composition and morphology are promising for a broad range of emerging applications in optoelectronics, biomedicine and catalysis, owing to the morphological merits of fiber-like nanostructures and structural attributes of π-conjugated polymers. Living crystallization-driven self-assembly (CDSA) of π-conjugated-polymer-containing block copolymers (BCPs) has emerged as an efficient strategy to prepare CPNFs with precise dimensional and structural controllability by taking advantage of the crystallinity of π-conjugated polymers. In this review, recent advances in the generation of CPNFs have been highlighted. The influence of the structure of π-conjugated-polymer-containing BCPs and experimental conditions on the CDSA behaviors, especially seeded growth and self-seeding processes of living CDSA, has been discussed in detail, aiming to provide an in-depth overview of living CDSA of π-conjugated-polymer-containing BCPs. In addition, the properties of CPNFs as well as their potential applications have been illustrated. Finally, we put forward the current challenges and research directions in the field of CPNFs.